Postoperative severe enteritis - Gardiol Roland, Valdo C (Cirugía del Uruguay, 2020)
A survey is carried out of the pathology, clinical patterns, diagnostic procedures, course and treatmént of severe post-operative enteritis of the necrotizing type. Cases are grouped into six clinical forms designed to fa.cilitate early diagnosis, the only way of instituting an adequate, life-saving therapy. Two diagnüstic elements are regarded as paramount: the search for soluble albumins and the pathological examination of the fecal centrifuged. Seven cases, of which four with pathological evidence, are submitted.